Fatal Sarcocystis falcatula Infection in Three Penguins - Kirejczyk, Shannon G. M.; Burns, Rachel E.; Hyatt, Michael W.; Yabsley, Michael J.; Ter Beest, Julia M.; Gyimesi, Zoltan S.; Ossiboff, Robert J.; Waltman, Amelia; Seimon, Tracie A.; McManamon, Rita (Frontiers in Veterinary Science, 2019)
Sarcocystis falcatula is a well-known cause of fatal pneumonia in some birds, particularly Old World psittacines. Here we describe fatal sarcosystosis due to S. falcatula in 3 penguins (Family Spheniscidae) under managed care, including one African penguin (Spheniscus demersus) and two Southern rockhopper penguins (Eudyptes chrysocome). Randomly distributed foci of necrosis, inflammatory cell infiltrates, edema, and variable numbers of round to elongated protozoal schizonts were observed in sections of lung. Protozoal organisms exhibited strong immunoreactivity for Sarcocystis sp. antigen by immunohistochemistry. Apicomplexan and Sarcocystis genus-specific PCR assays and sequence analysis confirmed Sarcocystis falcatula as the etiologic agent. These cases of fatal pneumonia attributed to S. falcatula expand the list of aberrant intermediate avian hosts, with particular implications for penguins